2001
DOI: 10.1080/09652140020021189
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and suicide in 14 European countries

Abstract: Aims. To test the hypothesis that a positive population-level relationship between alcohol and suicide is more likely to be found in dry drinking cultures (as indicated by consumption level) than in wet drinking cultures. Design. Gender-and age-speci c suicide rates in 14 western European countries were analysed in relation to per capita alcohol consumption employing the Box-Jenkins technique for time series analysis. The country-speci c estimates were pooled into low-, medium-and high-consumption countries. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 22 publications
5
64
1
10
Order By: Relevance
“…Alcohol has been linked to increased country-level suicide rates in Europe, Canada (Hintikka et al, 1999;Inelmen, Gazerro, Inelmen, Sergi, & Manzato, 2010;Landberg, 2008;Mann, Zalcman, Smart, Rush, & Suurvali, 2006;Ramstedt, 2001) and in Japan (Nakaya et al, 2007). Alcohol is also thought to be associated with higher rates of suicide in some Indigenous groups and in the Pacific, although empirical data on this relationship is scarce (De Leo, Milner, & Sveticic, 2012;Laliberté & Tousignant, 2009;Rubinstein, 1992).…”
Section: Alcohol (N = 17)mentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol has been linked to increased country-level suicide rates in Europe, Canada (Hintikka et al, 1999;Inelmen, Gazerro, Inelmen, Sergi, & Manzato, 2010;Landberg, 2008;Mann, Zalcman, Smart, Rush, & Suurvali, 2006;Ramstedt, 2001) and in Japan (Nakaya et al, 2007). Alcohol is also thought to be associated with higher rates of suicide in some Indigenous groups and in the Pacific, although empirical data on this relationship is scarce (De Leo, Milner, & Sveticic, 2012;Laliberté & Tousignant, 2009;Rubinstein, 1992).…”
Section: Alcohol (N = 17)mentioning
confidence: 99%
“…The article particularly focused on studies assessing economic strain (changes in national income, income inequality, unemployment and modernisation) and social bonds in society (such as relationship status, fertility/birth rates, gender role shifts, religion and migration). This narrative review also covered research into several other social-environmental factors shown to have an influence on suicide, including alcohol use in society (Ramstedt, 2001) and media reports of suicide (Pirkis & Blood, 2001a. Differences in access to lethal means used in suicide were also considered, as these have been shown to vary across social contexts (Ajdacic-Gross et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We used this model specification to estimate the relationship between the time series alcoholism and suicide mortality rates in this paper. In line with previous aggregate [16,17] we estimated semi-logarithmic models with logged output. The following model was estimated:…”
Section: Discussionmentioning
confidence: 99%
“…Han puesto de manifiesto que el efecto del alcohol sobre estos desenlaces depende de los patrones y la cultura de consumo de cada país, siendo la asociación más fuerte donde los atracones predominan sobre el consumo regular, como en el norte y centro de Europa [122][123][124][125] . Como se indicó, a partir de estos estudios se puede obtener el porcentaje de cambio en la frecuencia del problema por litro de alcohol consumido o combinar este porcentaje con el nivel total de consumo para encontrar la FAP-alcohol específica del país para ese problema 20 .…”
Section: Lesiones Y Conductas Violentas Relacionadas Con Alcoholunclassified